The Role Of Business Ethics In Increasing Profit At PD. Surya Medal Sumedang - Megah Dewi Anggini; Jaja Jaja (SINTESA, 2023)
The research focus contains the role of business ethics in increasing profits at PD. Surya Medal Sumedang. The purpose of this research is to find out how the application of business ethics and to find out how the role of business ethics in increasing profits in PD. Surya Medal Sumedang. This research is motivated by the important role of business ethics in increasing company profits. Not only seen from the achievement of profits, but also seen from the role of business ethics during the company's activities. Which is an important foundation for the company to continue to grow and be able to face competitors. With the implementation of business ethics, which is seen from business ethics according to economics and business ethics according to special regulations that apply. The method used in the research is descriptive qualitative with two variables, namely business ethics and increasing profits. Data collection techniques used are observations, interviews, documentation, and triangulation. Using data analysis Miles and Huberman (1984) namely data reduction, data display and conclusion drawing. As for the results and discussion, namely business ethics according to economics, the company has run it well, so the company can maintain its service quality, product quality to get a good image from many parties. And business ethics according to the special regulations that apply greatly affect the existence of the company if it complies with all the rules that have been previously agreed upon. The achievement of an increase in profits felt by the company, this is realized through the implementation of business ethics which is the main guideline or it can be said as the foundation for the business to be able to maintain its image, existence, product development, and reach a wider distribution system to various regions in Indonesia.